A srikaya-like light-harvesting antenna based on graphene quantum dots and porphyrin unimolecular micelles. Issue 60 (4th July 2016) - Liu, Yannan; Li, Shanlong; Li, Ke; Zheng, Yongli; Zhang, Meng; Cai, Caiyun; Yu, Chunyang; Zhou, Yongfeng; Yan, Deyue
Abstract : A novel hybrid light-harvesting antenna with a srikaya-like structure of multi-graphene quantum dots (GQDs) as donors and one porphyrin unimolecular micelle as the acceptor was constructed through electrostatic self-assembly. Abstract : A novel hybrid light-harvesting antenna with a srikaya-like structure of multi-graphene quantum dots (GQDs) as donors and one porphyrin unimolecular micelle as the acceptor was constructed through electrostatic self-assembly. The constructed antenna showed a high energy transfer efficiency of up to 93.6% and an antenna effect of 7.3 in an aqueous solution.